2014
DOI: 10.1371/journal.pone.0095101
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Allows Efficient and Complete Knock-In of a Destabilization Domain-Tagged Essential Protein in a Human Cell Line, Allowing Rapid Knockdown of Protein Function

Abstract: Although modulation of protein levels is an important tool for study of protein function, it is difficult or impossible to knockdown or knockout genes that are critical for cell growth or viability. For such genes, a conditional knockdown approach would be valuable. The FKBP protein-based destabilization domain (DD)-tagging approach, which confers instability to the tagged protein in the absence of the compound Shield-1, has been shown to provide rapid control of protein levels determined by Shield-1 concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 35 publications
(39 reference statements)
1
37
0
Order By: Relevance
“…Using CRISPR-based targeting, however, we were able to engineer "homozygously" DD-tagged clones in a single round of transfection even in cell lines that were triploid or tetraploid for the locus of interest. Together with a recent study that developed a similar approach but was restricted to a single gene and a single cell line (38), these findings indicate that the Degron-KI approach should be broadly applicable to many genes and cell line models.…”
Section: Discussionmentioning
confidence: 67%
“…Using CRISPR-based targeting, however, we were able to engineer "homozygously" DD-tagged clones in a single round of transfection even in cell lines that were triploid or tetraploid for the locus of interest. Together with a recent study that developed a similar approach but was restricted to a single gene and a single cell line (38), these findings indicate that the Degron-KI approach should be broadly applicable to many genes and cell line models.…”
Section: Discussionmentioning
confidence: 67%
“…These resources have broadly facilitated implementation of affinity capture/MS strategies in mammalian tissue culture systems (66,68). Although CRISPR-based methods (69–72) are increasingly enabling tagging of endogenous proteins, numerous methods employ an additional copy of a tagged transgene. Three popular approaches for human transgene expression that we commonly use are the Flp-In T-Rex system (Life Technologies), BAC transgenesis, and episomal transfections (73,74).…”
Section: Affinity Capture: Principlesmentioning
confidence: 99%
“…For example, it has now been demonstrated that destabilizing domains can be inserted upstream of exon 1 of Treacher Collins-Franceschetti syndrome1 (TCOF1) to conditionally regulate it by the addition of Shield-1 (Park et al, 2014). Because of the high efficiency of gene targeting, both alleles can be modified in a single cell leading to conditional regulation without interference from endogenous sources.…”
Section: Protein Stability Controlmentioning
confidence: 99%